3-2-1 bungy: A typology of performance styles. (November 2015) - Ferguson, Shelagh; Veer, Ekant
Highlights: A performance style typology is developed based upon the adventure paradox. Relational schemas of nature, culture and audience are problematic in bungy jumping. Dramaturgical analysis of re-performance takes a non-representational focus. Links extra-ordinary touristic experience to place, site, body and re-performance. Abstract: Understanding how people express themselves in everyday acts has been well examined since Goffman's (1959) seminal piece. His work laid the foundation for understanding performance and is used as the cornerstone for an established body of research concerning social performance in tourism (Coleman & Crang, 2002; Doorne & Ateljevic, 2005; Edensor, 2000; Haldrup & Larsen, 2009; Ness, 2007; Picarda & Zuevb, 2014). The context of bungy-jumping affords a rich resource to unpack the construction of performance styles due to the inherent contradiction of being simultaneously at risk and safe. Thus we develop a typology of performance styles where each proposed style becomes a function of the performer's interaction with the audience and the performer's belief in the adventure paradox.